Electrocardiographic Pattern of Pregnant Women with Advanced Maternal Age - Mangkoesoebroto, Arjatya Pramadita; Pramono, Besari Adi; Mochtar, Aruman Yudanto Ariwibowo Binarso (Faculty of Medicine, Diponegoro University, 2023)
Background: Advanced maternal age (AMA) is becoming increasingly common and is associated with increased maternal and fetal morbidity and mortality. Around 22,2% of maternal deaths were found to be from cardiovascular disease, and women with higher cardiovascular mortality were likely older. Electrocardiography (ECG) is a simple tool for detecting cardiovascular problems. Though there are many studies of the ECG in normal pregnant women, there is still limited data on the ECG pattern in pregnant women with AMA.Objective: Describe the characteristics of the ECG pattern in woman with AMA.Methods: This study used data retrospectively from medical records of patient in Kariadi General Hospital Semarang from 1st to 30th October 2018. The inclusion criteria were advanced age ³ 35 years, in the last trimester. Demography, clinical, laboratory , and 12-lead ECG data were collected and reported.Results: Thirteen patients were obtained, with mean age of 38,3 years. Majority of patients had preeclampsia (61,5%) and superimposed preeclampsia (15,4%). Mean systolic blood pressure was 168 mmHg. All of the patients was sinus rhythm, with a mean heart rate 92,5 bpm. Mean QTc was 430,7ms, with 3 patients (23,1%) having borderline prolongation grade. Another abnormality was a left atrial abnormality in 3 patients (23,1%), poor R wave progression in 2 patients (15,4%), and a pathological Q wave in 1 patients (7,7%).Conclusion: ECG abnormalities are seen in 38,4% of pregnant women over 35 years old. The performance of an ECG in AMA may be a first step toward improved pregnancy outcomes since it is widely available and easily interpreted by general practitioners.